The influence of sprint training on changes in the morphological and rheological properties of the blood - Chmielewska, K.; Ptaszek, B.; Teleglow, A. (Journal of Kinesiology and Exercise Sciences, 2017)
Aim. The aim of the work is to present morphological and rheological changes in the blood of sprinters under the influence of preparatory training for sport competitions. Basic procedures. The research was carried out among a group of 10 sprinters from the AZS AWF Krakow Sports Club within the 21-25 age group. The average duration of professionally performing track-and-field among the studied group was 6 years. The athletes were preparing for the Indoor Polish Track-and-Field Championship. 5 ml of blood was collected from the athlete`s ulnar vein before the preparatory season and just before the Polish Indoor Championship (after 121 days of training). Results. A statistically significant reduction in MCH [pg], MCHC [g/dl], fibrinogen [g/l] and AMP [au], and statistically significant increases in RBC [106/mm3], HCT [%], EI [Pa] for 0.58-15.98 [Pa] shear stress were found, while there were no changes in the aggregation of erythrocytes. Conclusions. Specialized sprint training has a positive effect on morphological and rheological changes in the blood.